THE PROCEDURES FOR DETERMINING LIABILITY AND SANCTIONS FOR FAILURE TO FULFILL THE OBLIGATIONS OF EU MEMBER STATES - Matijašević, Jelena; Alavuk, Marijana (Law - Theory and Practice, 2012)
EU member states and candidate countries must invest great efforts to ensure a full compliance with the acquis. When a member state of the European Union fails to fulfill its obligations under either the Treaty on the Functioning of the European Union or the Treaty on the European Union, it is obliged to take all necessary measures to achieve the result prescribed by the contracts, or, it is obliged to compensate the damage which is caused. Misdemeanor proceedings is considered to be the mechanism of public enforcement of EU law with the administrative center of the proceedings conducted by the Commission in order to reach an agreement by negotiation. The paper analyzes in details the articles of the TEU and TFEU relating to proceedings for determining liability for failure to fulfill the obligations of EU member states. The particular chapter is devoted to case law and sanctions which may be imposed in this field. In this regard, a particularly interesting question is the one referring to the purpose of sanctions – the lump sum and payment fines, their relation and the dynamics of the pronouncement.